Agglomeration, migration, and regional growth: A CGE analysis for Uganda - Dorosh, Paul A.; Thurlow, James (International Food Policy Research Institute, 2009)
Uganda has experienced rapid economic growth and poverty reduction over the past decade but has failed to significantly improve incomes in its northern regions where prolonged conflict has hindered growth. We consider three strategies to close this regional divide: (1) develop a north-south corridor to encourage regional trade, (2) accelerate growth in the southern capital city and encourage north-south migration, and (3) improve agricultural productivity in rural areas. We examine these strategies using a regionalized computable general equilibrium model, accounting for internal migration and productivity gains from urban agglomeration effects. Simulation results indicate that a north-south corridor benefits northern households, but its benefits are limited by the small size of northern urban centers and the low productivity of northern producers. Investing in the capital city accelerates economic growth but has little effect on other regions? welfare because of the city?s weak growth linkages with other regions and small migration effects. Improving agricultural productivity, however, though less effective at stimulating national economic growth, generates broad-based welfare improvements in both rural and urban areas. We therefore conclude that without significant gains in agricultural productivity in the next decade, out-migration and urban-led growth centered in Kampala will be insufficient to significantly reduce poverty in northern Uganda.